SYNERGY OF ISLAMIC RELIGIOUS EDUCATION IN SCHOOLS AND FAMILIES IN FORMING CHILDREN'S ISLAMIC PERSONALITY - Yusuf, Achmad (MSJ : Majority Science Journal, 2025)
This study examines the importance of synergy between Islamic religious education (IRE) in schools and families in forming children's Islamic personality. Using a literature review approach, this research analyzes the role of families as the first educational institution, the function of schools in strengthening religious education, and effective synergy models between these two environments. The results show that families play a role in instilling values of faith, worship, and noble character through exemplary behavior, habituation, and supervision. Schools strengthen this foundation through integrated IRE curriculum, Islamic school culture, and teacher exemplary behavior. Effective synergy between families and schools includes routine communication, joint programs, parental involvement in school activities, and coordination in implementing Islamic values. The synergy model based on maqāṣid al-sharīʿah shows that active collaboration between families and schools contributes significantly to forming a complete Islamic personality. This research recommends the need for formal agreements between schools and families, continuous training for teachers and parents, and the development of comprehensive assessment instruments to measure the effectiveness of children's Islamic personality formation.